Redesign Woodeco Stool - Jhon Viter Marpaung; Muhammad Fauzi; Desy Prastyani (JOURNAL OF APPLIED SCIENCE (JAPPS), 2021)
The concept applied to the design of stool furniture this time carries the theme that will be used, namely Scandinavian. A product that will be designed through trend analysis, through the uniqueness of the design owned. The uniqueness is presented through a combination of foreign and traditional cultures, being a style inspiration for designers and becoming the first choice product for the community in its needs. Qualitative methods with an event approach that is carried out make a direct source for designers to conduct a renewable data research so as to gain knowledge about the style and concept of a broader design to be applied to a design design this time. Market segmentation or User is intended is an urban society that has a standardization of modern living, as well as the characteristics of users who have uniqueness in a work such as creative workers oriented in the field of art or creative. This product is intended for families who have a modern lifestyle, with the implementation of modern product styles making this design has a concept of styling organic design that is combined with the application of batak toba motifs as the preservation of cultural products to preserve cultural knowledge to make their own scandinavian-style products